Facile Coating of HAP on Ti6Al4V for Osseointegration - Asrar, S.; Tufail, M.; Chandio, A. D. (Engineering, Technology & Applied Science Research, 2021)
Ti6Al4V alloy is a material with great strength, low-slung modulus, inferior density, and a virtuous blend of mechanical and exceptional corrosion resistance. However, it does not offer good osseointegration and bone development properties. Conversely, hydroxyapatite (HAP) is highly bioactive in nature to bind with the nearby bone tissues when implanted in the host body. In this work, we have extracted HAP from bovine bones by using the thermal decomposition method. This was followed by its deposition onto the Ti6Al4V alloy using the Electrophoretic Deposition (EPD) technique. TiO2 is used as a bond coat layer to increase the adhesion between HAP and Ti6Al4V alloy substrates. The coated samples after sintering exhibited excellent adhesion. This was followed by characterization using Scanning Electron Microscopy (SEM) and Fourier Transformed Infrared Spectroscopy (FTIR). FTIR and SEM confirm the formation of HAP and its presence after the immersion in SBF. Vicker hardness tester confirms the increase in hardness value of coated samples up to 35%. Potentiostat tests were conducted to compare the corrosion rate of both samples. In addition, the particle sizes were also identified by a laser particle analyzer, whereas X-Ray Diffraction (XRD) technique was also used to determine the crystalline phases of alloy and HAP.